L’OCTROI DES MICROCREDITS EN CÔTE D’IVOIRE: LE DEFI DE LA CONFIANCE ENTRE PRÊTEURS ET EMPRUNTEURS DANS UN CONTEXTE DE FRAGILITE POLITIQUE ET ECONOMIQUE - Parfait, N’goran Koffi; Félix, Grodji Kouamé (European Scientific Journal, ESJ, 2013)
This article shows that the scarcity of loans in the post-conflict context in Côte d’Ivoire is linked to the fall of the level of trust between the Institutions of Micro-finance and the borrowers. Most Institutions of Micro-finance practice under a form or under other one the individual loan and/or the collective loan called «credit of united deposit». Principally founded on a high supply of trust, this form of credit implicates, in principle, a less rigid control due to the collective commitment to reimburse the loan. But the sociopolitical crisis crossed by Côte d’Ivoire eroded the degree of trust between the Institutions of Micro-finance and the borrowers and made more difficult the access of the groups of joint and several guarantee to the microcredits.